Thin 3-D bandpass frequency-selective structure based on folded substrate for conformal radome applications - Omar, Ahmed Abdelmottaleb (2021)
A new design method based on a folded substrate is proposed in this paper to reduce the thickness of 3-D bandpass frequency-selective structure (FSS). A 67% and 79% thickness reduction compared to the basic 3-D bandpass FSS is achieved by employing three-layer and five-layer folded substrates, respectively. Single-and dual-polarized designs are presented. By integrating one more substrate with a different dielectric constant, dual-band thin structure is achieved. One structure with a five-layer folded substrate is designed, fabricated, and measured using the parallel-plate waveguide measurement setup. It has a center frequency of 3.57 GHz with 26.9% transmission bandwidth. The structure thickness is only 0.06λ , where λ is the free-space wavelength at the center frequency of the passband. Stable frequency response is achieved under oblique incidence. A good agreement is accomplished between simulated and measured results. Moreover, a semicylindrical radome is constructed based on the thin 3-D FSS and integrated with a broadband horn antenna. The radiation characteristics of the entire antenna-radome system are finally investigated and its good filtering feature is demonstrated. A fabricated prototype of this radome is measured in the presence of a broadband horn antenna.